Norway : Financial Sector Assessment Program-Technical Note- Stress Testing the Banking Sector. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note discusses results of banking sector stress tests on Norway. The Norwegian banking sector is generally well prepared to cope with possible external shocks, but imbalances have built up in recent years and could pose challenges. The stress-testing exercise included a comprehensive analysis of solvency and liquidity risks in the banking sector. The stress test results show that while the banking sector is highly resilient, it could experience challenges in case of severe macroeconomic shocks, as assumed in the adverse scenarios. The stress tests also illustrate that the banking system remains vulnerable to liquidity risks, due in part to scarce liquidity buffers in Norwegian krone.